Gajusz Waleriusz Maksymus czyli historia moralizująca,jej losy w dawnych epokach oraz polski przekład IV 1-15 - Lewandowski, Ignacy (Studia Europaea Gnesnensia, 2014)
Based on Facta et dicta memorabilia by Valerius Maximus, the author discusses a type of moralising history in the ancient times and selected examples of its fates in Antiquity, the Middle Ages, Renaissance and Baroque periods in Europe,Poland in particular. The quoted translations of excerpts from Book IV indicate the need to effect a Polish translation of the text.